Penerapan Metode Socrates Dalam Pembelajaran IPA Fisika Untuk Meningkatkan Ketrampilan Berpikir Kritis Peserta Didik Kelas VII SMP Negeri 4 Satu Atap Taliabu Timur Selatan - Wambes, Dwi Yanti (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2025)
This research was designed to optimize students' critical reasoning capabilities through the application of the Socratic method in the context of physics concepts in Natural Sciences (IPA). This study is categorized as Classroom Action Research (CAR). The focus of the study covered the dynamics of the learning process, with a total of 25 students participating. The study was organized into two comprehensive cycles: Cycle I and Cycle II. Each cycle involved a series of methodological stages: design (planning), implementation (execution), in-depth evaluation (observation), and self-evaluation (reflection). At the end of each cycle, a summative evaluation was conducted through a test, and the research instruments used included observation instruments dedicated to monitoring the activities of educators and students. This study indicates that the adoption of the Socratic approach contributed significantly to improving critical thinking capabilities in the student population. This was evident in students' more active engagement in dialogue and their courage to present rational arguments to support their answers. This quantitative change also showed an increase after the evaluation, whereas previously no participants met the passing criteria (0%). However, in the first cycle, there was a substantial improvement, with an average score of 47, achieving a 28% pass rate. In the second cycle, the average student score increased to 79, with the pass rate soaring to 76%. Based on these findings, it can be concluded that the implementation of the Socratic method has strong potential to optimize the critical thinking skills of seventh-grade students in Physics at SMP Negeri 4 Satu Atap Taliabu Timur Selatan.